Uncertainty and complementarity: Two key notions in Paul Busch's studies at the heart of quantum mechanics - Lahti Pekka (United Kingdom, 2025)
The problem of approximate joint measurement of complementary observables, like position and momentum, and the relevance of the uncertainty relations to that question were at the heart of the investigations of Paul Busch into the foundations of quantum mechanics. A good third of his published work dealt with this and closely related questions. This paper is an attempt to survey some of the steps taken in that research starting with Paul's first papers on the subject matter in the early 1980's and reaching its height in recent years.
Mathematical Foundations of Quantum Mechanics - in memoriam Paul Busch 18th - 19th June 2019, York, United Kingdom